2003
DOI: 10.1194/jlr.m200393-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the intestinal uptake of cholesterol, plant sterols, and stanols in mice

Abstract: The recent identification of the aberrant transport proteins ABCG5 and ABCG8 resulting in sitosterolemia suggests that intestinal uptake of cholesterol is an unselective process, and that discrimination between cholesterol and plant sterols takes place at the level of sterol efflux from the enterocyte. Although plant sterols are structurally very similar to cholesterol, differing only in their side chain length, they are absorbed from the intestine to a markedly lower extent. In order to further evaluate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 35 publications
6
67
1
Order By: Relevance
“…9) They thought that since sitosterol was rapidly excreted from intestinal cells to the intestinal lumen, the ratios of sitosterol/cholesterol decreased. However, our present results do not support this.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9) They thought that since sitosterol was rapidly excreted from intestinal cells to the intestinal lumen, the ratios of sitosterol/cholesterol decreased. However, our present results do not support this.…”
Section: Discussionmentioning
confidence: 99%
“…Igel et al administered various sterols and stanols as an oil suspension to mouse stomach. 9) The incorporated plant sterol and cholesterol at an early stage after administration were thought to be extremely low in quantity, because almost all of the suspension was assumed to be in the stomach. Hence, we infused a bile salt micelle containing sitosterol and cholesterol into the duodenum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were cultured in 75 cm 2 Falcon flasks in Dulbecco's modified Eagle's medium (DMEM) containing 25 mM glucose and supplemented with 10% heat-inactivated (561C) horse serum, 100 U/ml penicillin, 100 mg/ml streptomycin, 1% nonessential amino acids (Gibco, Invitrogen Corp., Cergy Pontoise, France). Cells were incubated at 371C in a humidified atmosphere with 5% CO 2 and subcultured to preconfluency after trypsinization (0.5% trypsin/2.6 mM EDTA).…”
Section: Cell Culturementioning
confidence: 99%
“…They are structural analogues of cholesterol. Numerous laboratory studies focused on their potential to reduce cholesterol absorption by the small intestine, [1][2][3][4] and cholesterol uptake by LDL. [5][6][7] In addition, it was reported that phytosterols prevent coronary heart disease, 8 and cardiovascular risks.…”
Section: Introductionmentioning
confidence: 99%